Expresión ¬(P∧(¬Q∨R))
El profesor se sorprenderá mucho al ver tu solución correcta😉
Solución
Solución detallada
¬(p∧(r∨¬q))=(q∧¬r)∨¬p
(q∧¬r)∨¬p
Tabla de verdad
+---+---+---+--------+
| p | q | r | result |
+===+===+===+========+
| 0 | 0 | 0 | 1 |
+---+---+---+--------+
| 0 | 0 | 1 | 1 |
+---+---+---+--------+
| 0 | 1 | 0 | 1 |
+---+---+---+--------+
| 0 | 1 | 1 | 1 |
+---+---+---+--------+
| 1 | 0 | 0 | 0 |
+---+---+---+--------+
| 1 | 0 | 1 | 0 |
+---+---+---+--------+
| 1 | 1 | 0 | 1 |
+---+---+---+--------+
| 1 | 1 | 1 | 0 |
+---+---+---+--------+
Ya está reducido a FND
(q∧¬r)∨¬p
(q∧¬r)∨¬p
(q∨¬p)∧(¬p∨¬r)
(q∨¬p)∧(¬p∨¬r)